Seroprevalence and Molecular Detection of Canine Leptospirosis in and around Navsari, South Gujarat, India - Kanthala, Sunayana; Patel, Dharmesh R.; Balamurugan, V.; Makwana, Pushpa M.; Parasana, Dixit K.; Chaudhary, Prahlad S.; Kalyani, Irsadullahkhan H. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Leptospirosis, an anthropozoonotic disease, is a growing global public health concern due to its increasing prevalence in both developing and developed countries caused by serovars of Leptospira. The present study was conducted to estimate the seroprevalence, and associated risk factors of leptospirosis in and around Navsari district (Surat and Valsad) of Southern Gujarat,India . The data was collected through a pretested questionnaire to detect the risk factors associated with disease occurrence. Samples were collected from 410 dogs (410 sera samples, 66 blood and 66 urine samples). Microscopic Agglutination Test (MAT) was conducted to determine the seroprevalence of predominant leptospirosis serovars. Out of 410 sera samples, 45 were found positive with seroprevalence of 10.98%, and serovar Pyrogenes followed by Shermani and Djasiman were found to be predominant. In ImmunoComb dot assay, out of 108 samples 53 (49.07%) were found positive for leptospiral antibodies. Overall seroprevalence was found to be 15.37% with MAT and ImmunoComb dot assay. A total of 6/66 (9.09%) blood and 4/66 (6.06%) urine samples were found positive by PCR using Primers lep1 & lep2 and LipL32 F and R showing amplicon band length at 331 bp and 242 bp, respectively. The overall prevalence of leptospirosis was found to be 16.59% by MAT, ImmunoComb and PCR. The risk factor analysis using a multivariable logistic model revealed that animals’ clinical status (χ2=7.7, p
Keywords: Canine leptospirosis; Molecular detection; Seroprevalence; South Gujarat